The art of memory forensics detecting malware and threats in Windows, Linux, and Mac memory - Ligh, Michael Hale; Case, Andrew (Digital forensics researcher); Levy, Jamie; Walters, Aaron (Wiley, 2014)
As a followup to the best-seller Malware Analyst's Cookbook, experts in IT security bring you a step-by-step guide to memory forensics-now the most sought after skill in the digital forensics and incident response fields. Beginning with introductory concepts and moving toward the advanced, The Art of Memory Forensics: Detecting Malware and Threats in Windows, Linux, and Mac Memory, teaches the art of analysing computer memory (RAM) to solve digital crimes.